PENGARUH JOB INSECURITY, JOB SATISFACTION DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION - AYUBBI, MUHAMMAD ANAS AL; TJAHJADI , KAREL (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to analyze and determine the influence of job insecurity, job satisfaction and work environment on turnover intention at PT. X. The population in this research is all non-management employees in the PT office. X as many as 92 employees. This research uses a non-probability sampling method with a saturated sampling technique. Data collection was carried out by distributing questionnaires to respondents. The data analysis method in this research is using multiple linear regression. Before testing the hypothesis, the data was analyzed using research instrument testing, classical assumption testing and model testing. The results of this research show that job insecurity influences turnover intention, while job satisfaction and the work environment do not influence turnover intention.